Competition Law and Europe's open Borders: The Case of Motor Vehicle Distribution in Switzerland - Simon J. Evenett; Michael Meier (Aussenwirtschaft, 2011)
This paper contains an independent3 empirical analysis of the effect of a Notice, issued by the Swiss Competition Commission in 2002 concerning vertical agreements between manufacturers and distributors ofmotor vehicles, on the degree to which the subsequent prices of cars in Switzerland exceeded those charged on the same models in neighbouring countries. Evidence presented here implies a non-transitory reduction in the degree of price discrimination against Swiss customers of medium- and large-sized cars in the years after the Notice came into effect.The total gain to Swiss buyers of cars is very conservatively estimated to be six times the total cumulative budget of the Swiss Competition Commission during the years 2003-2006; the best estimate of those gains exceed a quarter of a billion Swiss Francs during the same period. By 2006 the cumulative price reduction of the Swiss Competition Commission's action resulted in average savings permedium- and large-sized car that are estimated to be 929 and 2113 Swiss Francs, respectively.Moreover, the recurring annual gain to Swiss consumers of this single action by the Swiss Competition Commission is conservatively estimated to exceed ten times the latter's current annual budget, providing some indication of the "value for money" that effective competition law can have, even in economies with ostensibly open borders.
Keywords: 330